DASI-MU, Podcast-Based Dakwah at the Branch Board of Muhammadiyah Bangsalsari - Pribadi, Kukuh; Rahman, Miftahur (Journal Of Humanities Community Empowerment, 2024)
LSI survey results regarding self-identification as a member of Muhammadiyah or NU by Denny J.A. shows that the public who identify themselves as members of Muhammadiyah in 2023 will be 5.7%, which is down from 9.4% in 2005. This raises thoughts about the existence of Muhammadiyah in the digital realm so that it can be better known by the public. This is what underlies the DASI-MU service program to provide digital da'wah space on podcast channels so that Muhammadiyah's da'wah can be more widely known and makes it easier for the congregation to access da'wah content. This program is in collaboration with the Muhammadiyah Bangsalsari Branch Leader and in collaboration with Muhammadiyah Diktilitbang Mu-Research